Management of “Wernick’s Aphasia” through Ayurveda- A Case Study. - Elias, Liya; venu, Midun; Anand, P K V; Rahul , H (International Research Journal of Ayurveda & Yoga, 2023)
Aphasia is a language disorder caused by damage in a specific area of the brain that controls language expression and comprehension. It is most commonly seen in individuals post-stroke. Roughly 25%–50% of all strokes result in aphasia and 15 % of individuals under the age of 65 years experience aphasia after their first ischemic stroke. Treatments such as speech therapy can often help recover some speech and language functions over time, but many people continue to have problems in communicating. The signs and symptoms of Aphasia may be correlated with diseases such as Jihwasthamba and Ardita in Ayurveda. According to Acharya Yogaratnakara, the same treatment principles explained in Ardita Chikitsa have to be followed in Jihwasthamba. The article deals with a diagnosed case of Wernicke’s Aphasia and its management through Ayurveda. The description of this case aims to further the understanding of the benefits that this type of medicine may provide to poststroke patients living with aphasia. Here the line of treatment was not completely based on the classical Ardita Chikita, prime importance was given to the condition Aphasia. Assessments were taken before treatment and after treatment. Marked relief was noted in symptoms like aphasia, higher mental function, and memory. The recovery was promising and worth documenting.